2014
DOI: 10.2151/sola.2014-037
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Japan's Recent Temperature and Decadal Variability

Abstract: Since the late 1990s, surface temperature has been higher than (near or lower than) normal for summer/autumn (winter/spring) over Japan, indicating that the seasonal temperature contrast has become enhanced. In order to relate this to global-scale variability on decadal timescale, atmospheric re-analysis and ocean assimilation datasets were analyzed. It is suggested that the La Niña-like conditions which have been frequently observed in the tropical Pacific oceanic and atmospheric fields in the last decade hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(19 reference statements)
3
16
0
Order By: Relevance
“…In the first decade of the 21st century, surface temperatures in Japan have increased during summer and autumn (June-November, hereafter JJASON), and decreased during winter and spring (December-May, hereafter DJFMAM) [1]. Meanwhile, a negative phase of the Interdecadal Pacific Oscillation (IPO) [2,3] has been observed and is associated with conditions analogous to the La Nina phenomenon in the tropical Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first decade of the 21st century, surface temperatures in Japan have increased during summer and autumn (June-November, hereafter JJASON), and decreased during winter and spring (December-May, hereafter DJFMAM) [1]. Meanwhile, a negative phase of the Interdecadal Pacific Oscillation (IPO) [2,3] has been observed and is associated with conditions analogous to the La Nina phenomenon in the tropical Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a negative phase of the Interdecadal Pacific Oscillation (IPO) [2,3] has been observed and is associated with conditions analogous to the La Nina phenomenon in the tropical Pacific Ocean. Based on observations, atmospheric re-analysis, and ocean assimilation datasets, Urabe and Maeda [1] showed that the enhanced seasonal temperature contrast in Japan is associated with La Nina-like conditions and large-scale teleconnection patterns. This suggests that warming events during the summer and autumn may increase under negative IPO conditions, which goes against the global warming hiatus (i.e., a slowdown in the global surface temperature rise since the late 1990s) associated with negative IPO [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous attribution studies suggest that the changes in SSTs, GHG concentrations, and AA precursor emissions through aerosol-radiation and aerosol-cloud interactions are all important factors for the SFND pattern and associated drought over North and northeastern China (e.g., Kwon et al, 2007;Feng and Hu, 2008;Kosaka and Xie, 2013;Andrews, 2014;Gao et al, 2014aGao et al, , 2014bKamae et al, 2014aKamae et al, , 2014bQian et al, 2014;Song et al, 2014;Trenberth et al, 2014;Urabe and Maeda, 2014;Folini and Wild, 2015;Ueda et al, 2015;Wilcox et al, 2015;Zhang and Zhou, 2015). Previous studies have also revealed that decadal climate variability over East Asia is associated with low-frequency SST variability over the Pacific Ocean (e.g., Kwon et al, 2007, Kosaka andXie, 2013;Kamae et al, 2014a;Trenberth et al, 2014;Ueda et al, 2015) and Atlantic Ocean (Feng and Hu, 2008;Kamae et al, 2014a;Qian et al, 2014) via atmospheric teleconnections.…”
Section: Introductionmentioning
confidence: 99%
“…Urabe and Maeda (2014) indicate that positive subsurface temperature anomaly in the western tropical Pacific had been continuously accumulating along with the recent La Niña-like condition in decadal timescale. The subsurface temperature anomaly redistribution observed in the tropical Pacific in recent years (Figs.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…These variabilities observed in VAT pattern indicates that drastic changes have occurred not only at the sea surface but also in the ocean subsurface, associated with the development of El Niño including eastward propagations of warm Kelvin waves along the equator and westward propagations of cold Rossby waves in the off-equatorial region (Kessler 1990;White et al 2003;Hasegawa and Hanawa 2003). According to Urabe and Maeda (2014), the warm water in the western Pacific has continuously accumulated in the last decade. In 2015/16, zonally antisymmetric VAT anomaly pattern developed in the tropical Pacific with positive (negative) anomalies in the central to eastern (western) part.…”
Section: Observed Oceanic and Atmospheric Conditionsmentioning
confidence: 96%